Coronary Vulnerable and High-Risk Plaque: Current Concepts, Selective Preventive PCI, and an ISIC Position Statement - Muhammad Munawar; Aninka Saboe; Achmad Fauzi Yahya; Teguh Santoso; Abdul Hakim Alkatiri; Sunanto Ng; Sunarya Soerianata; Sodiqur Rifqi; Yudi Her Oktaviono; Nahar Taufiq; Janry Pangemanan; Sasmojo Widito; Muhammad Saifur Rohman; Muhammad Syukri; Doni Firman (The Indonesian Heart Association, 2026)
The concept of coronary vulnerable plaque has evolved from a histopathological concept into a potential therapeutic target for precision cardiovascular prevention. Recent evidence has expanded this paradigm beyond the traditional vulnerable-plaque construct towards the broader concept of high-risk plaque, encompassing rupture-prone plaques, erosion-prone plaques, calcified nodules, plaque burden, inflammatory activity, healing capacity, and patient-level susceptibility to thrombosis.Advances in Coronary Computed Tomography Angiography (CCTA), Intravascular Ultrasound (IVUS), Optical Coherence Tomography (OCT), Near-Infrared Spectroscopy (NIRS), molecular imaging, and Artificial Intelligence (AI) have substantially improved the detection and characterization of high-risk plaque. Circulating lipid, inflammatory, metabolic, and renal biomarkers provide complementary information regarding patient vulnerability. Concurrently, contemporary pharmacological therapy has substantially improved the natural history of coronary atherosclerosis by promoting plaque stabilization, fibrous cap thickening, lipid core regression, and attenuation of vascular inflammation.The emergence of preventive Percutaneous Coronary Intervention (PCI) for non-flow-limiting vulnerable plaques, particularly following the PREVENT trial, has reignited interest in focal treatment before clinical destabilization. Nevertheless, important uncertainties remain regarding patient selection, diagnostic thresholds, imaging strategies, device selection, long-term durability, cost-effectiveness, and applicability in resource-limited healthcare systems. Drug-Eluting Stents (DES) remain the most established device platform, whereas next-generation bioresorbable scaffolds and Drug-Coated Balloons (DCB) may offer future approaches to local plaque treatment without permanent metallic implantation. Although Coronary Artery Bypass Grafting (CABG) does not directly treat vulnerable plaques, it may indirectly protect selected patients with diffuse multivessel disease by bypassing plaque-bearing coronary segments.For Indonesia and other resource-constrained healthcare systems, future implementation should emphasize pragmatic implementation rather than widespread adoption of advanced technologies. Emphasis should remain on aggressive Optimal Medical Therapy (OMT), selective use of advanced imaging, careful identification of patients at the highest absolute cardiovascular risk, structured operator training, national registries, and rigorous evaluation of cost-effectiveness. The ultimate objective is not simply to detect more vulnerable plaques but to prevent more myocardial infarctions and cardiovascular deaths through efficient use of healthcare resources.The Indonesian Society of Interventional Cardiology (ISIC) recommends that aggressive systemic prevention, centered on OMT, should remain the foundation of care. Advanced plaque imaging and preventive PCI should be reserved for carefully selected patients with converging high-risk plaque characteristics, high patient-level risk, and a favorable benefit–risk profile.